2020
DOI: 10.1002/pssa.201900813
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Crystal Multilayer Nitride, Metal, and Oxide Structures on Engineered Silicon for New‐Generation Radio Frequency Filter Applications

Abstract: Molecular beam epitaxy is used for growth of structures with ScAlN for radio frequency filter applications. The nitride layers are grown directly on Si substrates for surface acoustic wave resonators, Lamb acoustic wave resonators, and on an epitaxial Mo on Er2O3 buffer layer on Si for film bulk acoustic resonators (FBARs). The crystal structure of the ScAlN layer is defined by Sc concentration. It can vary from wurtzite to hexagonal. Good crystal quality of the Mo layer results in low sheet resistance which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Moreover, ScAlN along with a Lamb acoustic wave resonator straightforwardly deposited on Si substrates at a resonance frequency of 9.02 GHz exhibits a figure of merit ( Q × k t 2 ) (9.1) and a higher coupling factor (4.8%). An FBAR application manufactured utilizing the nitride layer deposition on an epitaxial metal electrode exhibits the fundamental resonance frequency of 4.32 GHz . In addition, it is observed that yttrium oxide (Y 2 O 3 ) deposition is useful to upgrade both μ and I on of CNT-TFTs.…”
Section: Electronic Devicesmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, ScAlN along with a Lamb acoustic wave resonator straightforwardly deposited on Si substrates at a resonance frequency of 9.02 GHz exhibits a figure of merit ( Q × k t 2 ) (9.1) and a higher coupling factor (4.8%). An FBAR application manufactured utilizing the nitride layer deposition on an epitaxial metal electrode exhibits the fundamental resonance frequency of 4.32 GHz . In addition, it is observed that yttrium oxide (Y 2 O 3 ) deposition is useful to upgrade both μ and I on of CNT-TFTs.…”
Section: Electronic Devicesmentioning
confidence: 97%
“…An FBAR application manufactured utilizing the nitride layer deposition on an epitaxial metal electrode exhibits the fundamental resonance frequency of 4.32 GHz. 110 In addition, it is observed that yttrium oxide (Y 2 O 3 ) deposition is useful to upgrade both μ and I on of CNT-TFTs. By the composition of Al 2 O 3 passivation and Y 2 O 3 capping, unipolar CNT-TFTs with comparatively lower hysteresis (i.e., −30 V to +30 V), and low I off (∼pA) and high I on /I off (>10 7 ) at −10.1 V source-drain bias were accomplished, which are appropriate for active-matrix display driving.…”
Section: Electronic Devicesmentioning
confidence: 99%
“…A range of desirable physical, chemical, and mechanical properties of molybdenum (Mo), including a high melting point (2623 °C), a low density (ρ = 10.2 g cm –3 ), a large strength-to-weight ratio at high temperature, and an excellent conductivity (5.34 × 10 –8 Ω m at 20 °C), as well as versatile deposition methods, make Mo thin films attractive in various technical fields. For instance, Mo thin films act as efficient bottom electrodes in AlN-based bulk acoustic wave (BAW) devices or Cu­(In, Ga)­Se 2 thin film solar cells on both rigid and flexible substrates and show good chemical stabilities, low contact resistances, and high adhesion strengths due to the special textural structure and lattice matching with active layers. …”
Section: Introductionmentioning
confidence: 99%
“…The SAW sensor is a crucial element in military and civil electrical systems, such as in communication, navigation, radars, electronic countermeasures, telecontrol, telemetric systems, etc. To realize miniaturization and integration in SAW sensor fabrication, it is necessary to have interdigital transducers (IDT) and the corresponding electronic circuit on one chip (Fu et al, 2014;Bauer et al, 2015;Dargis et al, 2020). Nowadays, most of the SAW sensors are made on the piezoelectric crystal, which brings about difficulties in the integration and miniaturization (Lu et al, 2013;Mimura et al, 2017).…”
Section: Introductionmentioning
confidence: 99%